PENDIDIKAN KESEHATAN TENTANG MENGATASI KETIDAKNYAMANAN IBU HAMIL TRIMESTER III DI DUSUN RAI CEHET DAN RAI WASO: HEALTH EDUCATION ABOUT OVERCOMING THE DISCOMFORT OF PREGNANT MOTHERS TRIMESTER III IN RAI CEHET AND RAI WASO. - Manggul, Makrina Sedista; Trisnawati, Reineldis E.; Padeng, Efrasia P.; Banul, Maria S.; Senudin, Putriatri K.; Halu, Silfia A. N. (LPPM Univ. Ibn Khaldun Bogor, 2022)
ABSTRACT Background: Pregnancy is a normal process and must be given good attention so as not to cause complications to the mother and fetus. During pregnancy there are several changes both anatomically and physiologically. These physical changes cause discomfort or physical complaints during pregnancy. Situation analysis: From the results of interviews conducted with the team during a visit to the hamlets of Rai Cehet and Rai Waso, it was found that there are many pregnant women who think that the discomfort that occurs is abnormal and assumes that it can lead to complications for both the mother and the fetus. . This causes anxiety for the mother and family` Problem: Many pregnant women in the hamlets of Rai Cehet and Rai Waso do not understand how to deal with the discomfort that occurs during pregnancy. Solution: Providing health education to pregnant women about how to deal with discomfort during pregnancy Conclusion: After being given health education to pregnant women in the hamlets of Rai Cehet and Rai Waso, they have knowledge about the physiological changes that occur during pregnancy and how to overcome them. Keywords: Pregnant Women, Health Education, Discomfort.